Characterization of Acute Traumatic Coagulopathy in Cats and Association with Clinicopathological Parameters at Presentation - Gustin, Ursina; Sigrist, Nadja E.; Muri, Benjamin M.; Spring, Irina; Jud Schefer, Rahel (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective This study aimed to document rotational thromboelastometric (ROTEM) characteristics of traumatized cats and to investigate associations between clinicopathological parameters and acute traumatic coagulopathy (ATC). A secondary goal was to determine the relevance of autoheparinization in injured cats.Study Design Cats presenting with acute (<12 hours) trauma were eligible. Cats were allocated to the ATC group (≥2 hypocoagulable parameters) or non-ATC group (≤1 hypocoagulable parameter) based on ROTEM analysis. Clinicopathological parameters were compared between groups and regression was used to find variables associated with ATC. Heparinase-modified ROTEM (HepTEM) was used to assess for heparin effects in a subgroup.Results Fifty-three cats were included, and the incidence of ATC was 15%. Prolongation of both intrinsic and extrinsic clotting times (CT) was the most frequently altered ROTEM variable in the ATC group, but CTInTEM-prolongation also occurred in 47% of non-ATC cats. The incidence of autoheparinization, defined as concurrent CTInTEM prolongation and CTInTEM:HepTEM ratio >1.1, was 41% and was observed in both cats with and without ATC. None of the evaluated clinicopathological parameters were different between groups or associated with ATC.Conclusion Acute traumatic coagulopathy in cats is mainly characterized by prolonged CT. No relationship between clinicopathological variables and ATC was identified and prediction of ATC based on these variables was not possible. While autoheparinization is important in cats, it is not the sole cause for ATC.
Keywords: coagulation; ROTEM; trauma; autoheparinization; cat